2013
DOI: 10.1111/febs.12162
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the coordinated actions of estrogen receptors with epidermal growth factor receptor and insulin‐like growth factor receptor in the expression of cell surface heparan sulfate proteoglycans and cell motility in breast cancer cells

Abstract: Estradiol (E2)-estrogen receptor (ER) actions are implicated in initiation, growth and progression of hormone-dependent breast cancer. Crosstalk between ERs, epidermal growth factor receptor (EGFR) and/or insulin-like growth factor receptor (IGFR) is critical for the observed resistance to endocrine therapies. Cell surface heparan sulfate proteoglycans (HSPGs) are principal mediators of cancer cell properties and the E2-ER pathway as well as those activated by EGFR and IGFR have significant roles in regulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 44 publications
4
44
0
11
Order By: Relevance
“…There is still controversy over the expression of syndecans in cancer. The Karamanos group showed that syndecans-2 and -4 as well as glypican-1 were overexpressed in the breast cancer lines compared to normal mammary cells (Tsonis et al, 2013). In contrast, Vicente et al reported that syndecan-2 was highly expressed and the mRNA expression level of syndecan-1 and -4 were…”
Section: Discussionmentioning
confidence: 98%
“…There is still controversy over the expression of syndecans in cancer. The Karamanos group showed that syndecans-2 and -4 as well as glypican-1 were overexpressed in the breast cancer lines compared to normal mammary cells (Tsonis et al, 2013). In contrast, Vicente et al reported that syndecan-2 was highly expressed and the mRNA expression level of syndecan-1 and -4 were…”
Section: Discussionmentioning
confidence: 98%
“…In earlier studies, we had noted that E2/ERα signaling pathway makes a key partner of the receptors for EGF and IGF as to regulate the expression of ECM components in breast cancer cells [19][20][21][22]. In the present study, we provide data to show that induced loss of ERα results in potent EMT, striking changes in the expression profile of specific matrix macromolecules and in breast cancer cell's functional properties associated with an aggressive potential, highlighting the potential nodal role of ERα and matrix effectors in endocrine breast cancer resistance.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Other potentially critical factors that may be relevant in TNBC include the interplay between EGFR and insulin-like growth factor receptor signaling systems and production of cell surface effectors such as the subclass of heparin sulfate proteoglycans known as syndecans (52)(53)(54)(55)(56). Understanding how these different factors are integrated to drive metastatic progression will provide the Somewhat surprisingly, our data also appear to exclude a role for autocrine IL-6 because EMT programs fail to diminish the ability of NME cells to activate STAT3 in response to exogenous IL-6.…”
Section: Figure 4 Emt Inhibits Egfr-dependent Stat3 Signalingmentioning
confidence: 99%